Insight into high electrochemical activity of reduced La0·3Sr0·7Fe0·7Ti0·3O3 electrode for high temperature CO2 electrolysis. (1st February 2020) - Cao, Zhiqun; Wang, Zhihong; Li, Fengjiao; Maliutina, Kristina; Wu, Qixing; He, Chuanxin; Lv, Zhe; Fan, Liangdong
Abstract: Electrochemical reduction of CO2 under the high temperature electrolysis condition with favored kinetics is a promising method to utilize and convert CO2 to valuable chemicals and to reduce its environmental impact. In this work, the electrochemical performance of perovskite-type La0·3 Sr0·7 Fe0·7 Ti0·3 O3 (LSFT) oxide was thoroughly investigated as a cathode for high temperature solid oxide electrochemical reduction under practical CO2 electrolysis conditions of various current densities, partial pressures, and different CO–CO2 mixtures. The rate-limiting step of CO2 reduction on the LSFT surface was determined by the electrochemical impedance spectroscopy technique with a three-electrode configuration. The exceptional performance of LSFT cathode is confirmed as reflected by the low polarization resistance and the extremely low activation energy. Moreover, improved electrode performance is also obtained on the reduced LSFT sample under reducing atmosphere with CO, while the rate-determining step is not changed. It is also confirmed that the reduced LSFT cathode gives increased surface oxygen vacancy concentration which is believed to serve as accommodation for chemical adsorption and consequently the active sites for electrochemical activation of CO2, leading to the improved electrochemical performance. Highlights: Electrochemical activity under practical CO2 reduction condition is studied. Cathode polarization of LSFT for CO2 reduction is verified with 3-electrode study. LSFT shows super-low polarization and activation energy for CO2 reduction in SOEC. Reduced LSFT with increased oxygen vacancies benefits the HT chemical adsorption and activation.